TAp73 expression and P1 promoter methylation, a potential marker for chemoresponsiveness to cisplatin therapy and survival in muscle-invasive bladder cancer (MIBC). Issue 17 (2nd September 2019) - Bunch, Brittany; Krishnan, Nithya; Greenspan, Rebecca D.; Ramakrishnan, Swathi; Attwood, Kristopher; Yan, Li; Qi, Qianya; Wang, Dan; Morrison, Carl; Omilian, Angela; Bshara, Wiam; Pili, Roberto; et al.
ABSTRACT: Intrinsic and/or acquired resistance to cisplatin is a significant obstacle in the treatment of muscle-invasive bladder cancer. p73, a p53 homolog and determinant of chemosensitivity, is rarely mutated in bladder cancer (BC). However p73 expression and therefore function can be repressed through epigenetic changes. In this study, we sought to identify DNA methylation status of p73, expression of TAp73 isoform, and their role in cisplatin sensitivity in BC. Primary tumor samples from 338 bladder cancer patients showed decreased TAp73 expression in MIBC compared to superficial BC. Low TAp73 protein expression was associated with shorter overall survival. To investigate if the loss of expression was methylation dependent, we utilized Illumina 450K methylation arrays to interrogate over 150 BC patient samples. We found 12 distinct CpGs in the p73 gene locus that were hypermethylated in tumors compared to adjacent normal tissues. Patients with high p73 promoter methylation specifically at CpG site cg07382920 had worse survival. In vitro, treatment with a DNA demethylating agent, decitabine (DAC), decreased TAp73 methylation and upregulated expression in both CR-T24 (cisplatin resistant T24 cells) and wild type T24 cells. Furthermore, treatment with DAC increased cisplatin response in wild type T24 and CR-T24. Our studies indicate that TAp73 expression and P1 promoter methylation, specifically at the cg073892920 site, may have prognostic and diagnostic value in MIBC. In the setting of P1 promoter hypermethylation, DAC could be used as a potentiating agent of cisplatin-based chemotherapy.